PENGUKURAN TINGKAT KEMATANGAN SISTEM INFORMASI TAHANAN POLDA SUMSEL MENGGUNAKAN FRAMEWORK COBIT 2019 - Nabila Rizky Oktadini; Fiqih Alfito (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2023)
The South Sumatra Police Prisoners Information System is an application or technology used by the South Sumatra Regional Police, especially at the Directorate of Detainees and Evidence or Dittahti. The system was only launched about a year ago and there is no governance oversight yet. For this reason, the level of system maturity measurement is carried out to find out what needs to be improved so that governance at Dittahti runs well. Measurement of the maturity level of information systems is a guide or framework derived from COBIT 2019. At the beginning of the research, the discovery of organizational goals is then mapped into the COBIT 2019 Enterprise Goals. The next stage is mapping the company goals that have been obtained to the alignment goals. Furthermore, the alignment objectives obtained are mapped to the COBIT 2019 objectives. Then the problems obtained will be mapped to the recommended objectives. There are three objectives obtained, namely APO01, APO04, and APO11. Each objective is measured for its capabilities through a questionnaire based on COBIT 2019. The results of the capability level of each selected objective will be calculated on average so as to produce a maturity level. The maturity level obtained is level 1. The final stage of providing recommendations based on the results of the calculation of the current maturity level (as is) with the expected maturity level (to be). Recommendations for improvement are expected to help improve governance at the Dittahti of the South Sumatra Police.